Topical Issues of Influenza Vaccine Prevention - Firuza Ch. Shakhtakhtinskaya; Leyla S. Namazova-Baranova; Marina V. Fedoseenko; Tatiana A. Kaliuzhnaia (Вопросы современной педиатрии, 2021)
Influenza vaccination coverage has been expanding in recent years in Russian Federation. The topicality of influenza vaccination becomes more significant now at the beginning of seasonal increase in its prevalence, moreover, along with active immunization against coronavirus infection. Vaccination is crucial part in combined program of influenza prevention and control. Nowadays, the priority in influenza prevention is quadrivalent vaccines that can ensure the development of the most stable immunity. Russia has all the necessary resources to create and effectively implement modern influenza vaccines that meet international standards. Despite the remaining difficulties in combating influenza, preventive vaccination is by far the most effective method of protection that has proven its safety and efficacy.